To sing the body electric: Instruments and effort in the performance of electronic music. - d'Escriván, Julio (Contemporary Music Review, 2006)
Visualized emotion can be transmitted through minimal physical gestures in a musical performance; this process can be described as ‘sentic’, a term originally coined by Manfred Clynes in the 1970s during research into the effects of space travel. The development of alternate musical instruments from the 1960s up to the present day breaks the traditional musical paradigm of effort in performance. This development also shadows concepts of space exploration technology such as teleoperation. Musical instruments can be evaluated in terms of a new musical effort paradigm; a young generation seems content to accept that there may be no apparent correlation between input effort and sound output. This article explores what a contemporary notion of effort might be, inspired by a reading of Walt Whitman's poem ‘I Sing the Body Electric’.